Auto-Resistance to Seeds Germination of Invasive Acacia saligna Trees at Al-Jabal Al-Akhdar region - Salih , Sami Mohammed (Scientific Journal for Faculty of Science-Sirte University, 2021)
Sustaining the vegetation cover in Libya represents the most important priority that must be taken into account by the Ministry of Agriculture. This study was conducted in the laboratory of the Department of Biology, Faculty of Education, Omar Al-Mukhtar University, Al-Bayda, Libya, to investigate the possibility of controlling seed germination of Acacia saligna trees by using aqueous extracts (flower- seeds- leaves - bark) at different concentration (10, 20 and 40%). The results showed highly significant differences in decreasing a germination percentage and increasing an average germination time, between aqueous extracts and concentrations relative to control, where a flowers extract gave the largest effect on inhibitory germination percentages over the rest of other extracts. Commonly 40% concentration was the most toxic effect on A.saligna seed germination. The study concluded of Acacia salgina trees possess an autotoxicity that can be used to combat thier invasion and expansion in agricultural lands.